Relationship between Peer Pressure and Risk of Eating Disorders among Adolescents in Jordan - Nihaya A. Al-sheyab; Tamer Gharaibeh; Khalid Kheirallah (Hindawi Limited, 2018)
Background. The prevalence of disordered eating behaviors (DEBs) have increased worldwide. It is estimated that about 31.6% of Jordanian adolescents developed DEB. Engaging in peer groups is a prominent event in which adolescents try to belong to peers as part of exploring their social identity. Purpose. To assess the relationship between risk of eating disorders and peer pressure among adolescents. Methods. A descriptive, correlational, cross-sectional design utilized multistage cluster sampling technique was used to recruit students from 8th to 10th grades from both sexes from schools in northern Jordan. Data were collected from a self-administered, online questionnaire which was given to 738 participants. Results. The difference in overall mean of the Inventory of Peer Influence on Eating Concerns (I-PIEC) between adolescents with disordered eating behaviors and normal eating behaviors states was statistically significant. Scores for interaction peer pressure means were statistically higher for girls than for boys; conversely, likeability mean scores were statistically higher for boys than girls. Conclusions. The current findings suggest that healthcare professionals are encouraged to conduct appropriate school-based primary prevention for disordered eating behaviors.